(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
The study aimed to identify the art of journalistic investigation in the Syrian daily Al-Thawra newspaper, by knowing the nature of the topics covered by journalistic investigations, revealing their trends, sources, and geographical scope, in addition to monitoring the types of press investigations, headlines, and photos used during the study period. The study used the media survey method, and the data was collected using the content analysis form tool, and the sample was drawn in a comprehensive inventory of all journalistic investigations in Al-Thawra newspaper during the first half of 2022. The results of the study showed that most of the press investigations in Al-Thawra newspaper dealt with economic and service issues, and the newspaper relied on inquiry and investigation in dealing with various events and issues, and he often makes the negative on the topics of the journalistic investigation, and it relied in its Sources of citizen complaints, its press coverage focused on various Syrian governorates, as the explanatory title appeared in most press investigations, and the objective images accompanying the press investigations dominated during the study period, the study recommended the need to interest in journalistic investigations and understand their roles and functions, And developing the professional aspects related to preparing and editing the journalistic investigation.